From Pugwash to Putin : A Critical History of US-Soviet Scientific Cooperation - Sher, Gerson S., 1947- (Book collections on Project MUSE., 2019)
"For 60 years, scientists from the United States and the Soviet Union participated in state-organized programs of collaboration. From the first scientific exchanges of the Cold War years through the fall of the Soviet Union, Gerson S. Sher, a former manager of these cooperative programs, provides a detailed and critical assessment of what worked, what didn't, and why it matters"--